Editor-in-Chief’s Note - Elguja Khintibidze, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2026)
Editor-in-Chief’s Note The Byzantine Edifying Story of Barlaam and Joasaph, which gained widespread popularity among European peoples in the pre-Renaissance period through its Latin translation, remains a central subject of inquiry in contemporary medieval studies. Questions surrounding its composition and authorship continue to be the focus of ongoing research by scholars of Byzantine and Georgian Studies. Numerous studies on this subject have been published in previous issues of the journal The Kartvelologist. In 2024 (April 11–13), Tbilisi State University hosted an international conference titled "Georgian Balavariani and Byzantine The Story of Barlaam and Ioasaph." Selected conference papers were subsequently published in a digital volume under the same title (Tbilisi, 2024), including: Gaga Shurgaia, "The So-Called 'Lemma' of the Romance of Barlaam and Joasaph (CPG 8120) as Paratext"; Elguja Khintibidze, "Some News on the Creation of the Greek Story of Barlaam and Ioasaph"; "Georgian Redactions of Balavariani and Their Interrelationship"; I. Makaradze, "On the Sources of The Story of Barlaam and Ioasaph"; "Typology of Transformation of Anthroponyms in the Arabic, Georgian, and Greek Redactions of the History of Barlaam and Ioasaph"; Kote Lomidze, "On the Diplomatic Transcription of the Long Version of the Georgian Balavariani" The second part of the research presented at the conference is published in this issue. In 1996, Portuguese researcher M.I. Pérez discovered and examined a previously unknown redaction of the Greek Barlaam romance (The History of Barlaam and Joasaph), which R. Volk published in a critical edition in 2006. The majority of articles in this issue are devoted to studying this redaction. The text is presented here with translation and two sharply contrasting scholarly interpretations. Nature of the Issue The present volume includes both full-length research articles and shorter conference reports, reflecting the varied formats of academic exchange at the conference. This diversity allows us to present a comprehensive picture of current scholarship on Barlaam and Josaphat across different disciplines and methodologies. Bibliographic Format Given the multilingual and cross-cultural nature of research on Barlaam and Josaphat, this issue encompasses scholarship drawing on sources in multiple languages, including Georgian, Greek, Latin, Arabic and others. Consequently, bibliographic references in some articles follow citation conventions specific to their respective scholarly traditions rather than the journal's standard APA format. Each article maintains internal consistency in its citation system, and we have prioritized preserving the integrity of specialized bibliographic practices, particularly for non-Western sources where APA conventions may not adequately represent the scholarly apparatus. We believe this approach best serves the international scholarly community working on this important medieval text and its transmission across linguistic and cultural boundaries. Elguja Khintibidze